Mesoscale Eddy Effects on Nitrogen Cycles in the Northern South China Sea Since the Last Glacial - Chen, Miao; Zhao, Xiaoxiao; Li, Da-Wei; Dong, Liang (Frontiers in Earth Science, 2022)
Archaeal ammonia oxidation is the most important intermediate pathway in regulating the oceanic nitrogen cycle; however, the study of its specific role on a geological time scale is restricted to a specific part of marginal seas; thus far, only in the southern South China Sea (SCS). To explore the spatial pattern of the role of archaeal ammonia oxidation in the SCS, the GDGT-[2]/[3] ratio (Glycerol Dialkyl Glycerol Tetraether), an indicator of the archaeal ammonia oxidation rate, was analyzed and examined from the collected data profiles since the last glacial period in the northern SCS. The results showed that the GDGT-[2]/[3] ratio in the northern SCS was opposite to that in the southern SCS, with higher GDGT-[2]/[3] values during the Holocene compared to the last glacial period. Based on existing published depths of thermocline (DOT) data in the northern SCS since 30 ka, we believe that hydrological structural variations induced by mesoscale eddies caused this difference. Therefore, physical processes are very important factors that control the nitrogen cycle over a long-time scale. This study may provide new insights into the understanding of the role of archaeal ammonia oxidation within the marine nitrogen cycle over geological time scale.